2019
DOI: 10.3390/ijerph16050815
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid-Like Granulomatous Disease: Pathologic Case Series in World Trade Center Dust Exposed Rescue and Recovery Workers

Abstract: Sarcoid-like granulomatous diseases (SGD) have been previously identified in cohorts of World Trade Center (WTC) dust-exposed individuals. In the present studies, we analyzed lung and/or lymph node biopsies from patients referred to our clinic with suspected WTC dust-induced lung disease to evaluate potential pathophysiologic mechanisms. Histologic sections of lung and/or lymph node samples were analyzed for markers of injury, oxidative stress, inflammation, fibrosis, and epigenetic modifications. Out of seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…The average annual incidence increased initially from 15/100,000 in the 15 years prior to 9/11 to 85/100,000 in the year after 9/11 and then stabilized at 25/100,000 after 2002. Similar findings were reported in both survivor and non-FDNY rescue/recovery cohorts [60][61][62]. Unlike pre-9/11 sarcoidosis cases within the FDNY cohort, those with newly diagnosed sarcoidosis post-9/11 were more likely to have new asthma symptoms and airway hyperreactivity [59].…”
Section: Wtc-related Sarcoidosissupporting
confidence: 73%
“…The average annual incidence increased initially from 15/100,000 in the 15 years prior to 9/11 to 85/100,000 in the year after 9/11 and then stabilized at 25/100,000 after 2002. Similar findings were reported in both survivor and non-FDNY rescue/recovery cohorts [60][61][62]. Unlike pre-9/11 sarcoidosis cases within the FDNY cohort, those with newly diagnosed sarcoidosis post-9/11 were more likely to have new asthma symptoms and airway hyperreactivity [59].…”
Section: Wtc-related Sarcoidosissupporting
confidence: 73%
“…A summary of studies included in the review is shown in Table 2 Out of the nine studies reviewed, six evaluated the exposure among the 9/11 WTC responders or firefighters and their risk of sarcoidosis. Three out of the six studies that focused on WTC cohort were case series (17)(18)(19). Two studies were specific to the chemical composition of particulate exposure that they assessed which was silica dust (4,7).…”
Section: Resultsmentioning
confidence: 99%
“…One recent study has reported that former WTC responders also developed pulmonary fibrosis and the adjusted hazard ratio was nearly 5-times higher in those with a very high level of exposure, and nearly 3-times higher in those with a medium level of dust exposure 121 . In addition to fibrotic changes, several former WTC dust-exposed workers were also reported to develop sarcoid-like granulomatous diseases 122 .…”
Section: Exposure To World Trade Centre (Wtc) Dustsmentioning
confidence: 99%